PENGUATAN CITRA MEREK BATIK DENGAN TIPOGRAFI VERNACULAR - Murtono, Taufik (Institut Seni Indoensia Surakarta, 2014)
This study aims to design a brand identity of batik with vernacular typography. Vernacular typographyis typography with daily life character that is familiar with the activities of local community.Vernacular typography is used in this study because the types that are created by the previous researchdo not meet the needs of the product owners at batik center in Bayat, Klaten District. Themethod used is descriptive qualitative research to find qualitative data that is used as the base of thevernacular typography creating through the design process which is divided into four stages. Thestages covers assimilation, such as the collection and arrangement of information problem that isbeing studied; general studies, such as investigating the characteristics of the problem and possiblesolutions as well as tools and support materials; developing, creating and modifying; communicationconcerning the creative presentation of one or more solutions to the people inside and outside of theresearch team. Small scale industries such as batik center Bayat have disadvantages in accessingcreative sources because of the limited capital and opportunity. Therefore, this study becomes a helpfulthing in designing the brand identity for small industries. The results obtained include vernaculartypography design that is traced from the surrounding environment so that they produce specialtypefaces for example typographic style of batik motif, street-style typography, typographic styleengraving, handwriting-style typography, and free-style typography. Typographies that are generatedsubsequently applied in developing batik brand identity. Keywords: Typography, vernacular, brand, batik